Ultra-early neurologic outcome prediction of out-of-hospital cardiac arrest survivors using combined diffusion-weighted imaging findings and quantitative analysis of apparent diffusion coefficient. (1st March 2020) - Park, Jung Soo; In, Yong Nam; You, Yeon Ho; Min, Jin Hong; Ahn, Hong Joon; Yoo, In Sool; Kim, Seung Whan; Lee, Jin Woong; Ryu, Seung; Jeong, Won Joon; Cho, Yong Chul; Oh, Se Kwang; et al.
Abstract: Aim: This study examined whether the presence of cortical necrosis (CN) on ultra-early diffusion-weighted imaging (DWI) and the severity of cytotoxic oedema (CytE) with cerebral oedema (CbrE), measured using quantitative analysis of apparent diffusion coefficient (ADC), could predict neurological outcomes before targeted temperature management in out-of-hospital cardiac arrest survivors (OHCAs). Methods: In this retrospective study, the first DWI with ADC scans was performed within 6 h; the second was obtained between 72 and 96 h after return of spontaneous circulation. The primary outcome was neurological outcomes at 6 months after OHCA. The % voxels of ADC value (PV) was calculated; CbrE and CytE values were > or < than 650 −6 mm 2 /s, respectively. The best performance PV was obtained from CytE (thld-CytE) and CbrE values (thld-CbrE). Prognostic performances of CN, thld-CytE, thld-CbrE, and converted scores were calculated in combination. The changes in DWI findings and the difference between the PV (ΔPV) from the first and second DWI were analysed. Results: Thirty-six patients were included. CN (area under receiver operating characteristic curve [AUC] = 0.800), thld-CytE (PV420; AUC = 0.730), and thld-CbrE (PV1090; AUC = 0.775) showed meaningful performance, and the combined score showed best performance for poor outcome prediction (AUC = 0.956). DWI findings of CN patients was worse at the second DWI. ΔPV significantly increased in the poor outcome group, CN patients, and the group including both, thld-CytE and thld-CbrE. Conclusions: In OHCAs, ultra-early DWI with ADC could successfully predict poor neurological outcomes by combining scores of CN, thld-CytE, and thld-CbrE.